Petrous Carotid to Upper Posterior Circulation Bypass for the Treatment of Basilar Trunk Aneurysm: A Novel High-Flow Intracranial–Intracranial Skull Base Bypass for Posterior Circulation. Issue 3 (9th March 2023) - Wang, Xuan; Tong, Xiaoguang; Liu, Jie; Shi, Minggang; Shang, Yanguo; Wang, Hu
Abstract : BACKGROUND: Basilar trunk aneurysms are the most surgically challenging, and the spectrum covers small fusiform to dolichoectatic aneurysms and may lead to rupture, brain ischemia, or direct brainstem compression. The current strategy remains cerebral revascularization coupled with aneurysm trapping. Available bypass options for upper posterior circulation (UPC) are based on (1) different flow volumes from diverse blood supplies and (2) distinct modulation purposes for cerebral revascularization; however, the potential compromise of eloquent perforators of the basilar trunk and the occurrence of fatal brainstem infarcts remain unacceptable. OBJECTIVE: To innovate a high-flow intracranial–intracranial skull base bypass for posterior circulation to afford robust retrograde flow and shorten the graft length. METHODS: We retrospectively reviewed our experience in the treatment of a patient with basilar trunk aneurysm and reported a novel bypass alternative supplied by petrous internal carotid artery to augment blood flow to the UPC by a pretemporal approach. RESULTS: The postoperative course was uneventful, and there was no pons or midbrain ischemia or other complications. Postoperative computed tomography angiogram revealed the patency of bypass. There was no further development or rerupture observed during follow-up. CONCLUSION: Petrous internal carotid artery as a donor site is a reliable bypass modality for UPC. This approach provides the utmost retrograde flow to alleviate the development of dissecting aneurysms, preserves eloquent perforators of the basilar trunk, maintains bypass patency, and shortens the graft course. Therefore, this novel therapeutic alternative could be beneficial for improving the prognosis of basilar trunk aneurysms.